Implementasi Nilai Keislaman dari Hikmah Kisah Anak dalam Al-Qur’an di TK Yahdina Panyabungan - Selvina Armiah; Nurmaliana Harahap; Nova Elliza (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the implementation of Islamic values sourced from children's stories in the Qur'an in learning and habituation activities at Yahdina Panyabungan Kindergarten. A descriptive qualitative approach was used with observation, interview, and documentation techniques. The results showed that teachers used the story of Prophet Yusuf, Prophet Ismail, and the story of Luqman to convey the values of honesty, patience, and obedience to parents. These values are internalised through the storytelling method, daily habituation such as praying together, memorising hadith, and sharing activities. The main obstacle in this implementation is the lack of focus of some children during the activities. This research shows the importance of the narrative approach and habituation in instilling Islamic values from an early age.